2017
DOI: 10.1186/s12877-017-0679-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between social capital and health-related quality of life among left behind and not left behind older people in rural China

Abstract: BackgroundThe association between social capital and health-related quality of life (HRQoL) has not been thoroughly studied among older persons in rural China, especially among those who were left behind or not. This study investigates the association between social capital and HRQoL and examines possible differences of this association between being left behind or not in rural China.MethodsA cross-sectional survey of 825 people aged 60 years and older, residing in three rural counties in Jiangsu Province in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 35 publications
(51 reference statements)
0
27
1
Order By: Relevance
“…Forlani et al and Houtjes et al pointed out that the gender, age, and the educational level were related to the physical and mental health of the elderly [16,17]. Williams et al pointed out that religious beliefs, educational level, marital status, and family support can affect the quality of life of the elderly [18,19]. Xie et al showed that types of chronic diseases, living style, and financial support of children of the left-behind elderly in rural areas are influencing factors of mental health [20].…”
mentioning
confidence: 99%
“…Forlani et al and Houtjes et al pointed out that the gender, age, and the educational level were related to the physical and mental health of the elderly [16,17]. Williams et al pointed out that religious beliefs, educational level, marital status, and family support can affect the quality of life of the elderly [18,19]. Xie et al showed that types of chronic diseases, living style, and financial support of children of the left-behind elderly in rural areas are influencing factors of mental health [20].…”
mentioning
confidence: 99%
“…Based on this comparison the health prospect of rural population is weaker than the health prospect of the urban population in Australia as well [64]. The health chances of the rural old people and mainly the chances of the left behind old people in the countryside cannot reach the level of the urban old people in China [65]. Basic health care is hardly provided in Hungarian urban areas as well where an increasing number of medical doctors and dentists working in the basic health care are missing [66].…”
Section: Differences In the Living Standards Of Rural And Urban Lifementioning
confidence: 94%
“…Because of the increasing popularity of leaving the elderly behind, more researchers are now focusing on this special population [ 4 , 5 ]. It is clear that those left behind suffer from poorer mental and physical health outcomes, such as depression, anxiety, and cognitive impairment [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that those left behind suffer from poorer mental and physical health outcomes, such as depression, anxiety, and cognitive impairment [ 6 ]. Almost all of the existing research is focused on describing the mental health of these individuals [ 4 6 ]. Very little evidence is available on the relationship between left-behind status and the prognosis of special chronic diseases [ 7 ], especially that of myocardial infarction, which has increasingly gained importance as a serious health condition.…”
Section: Introductionmentioning
confidence: 99%